2009
DOI: 10.2214/ajr.08.1254
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Arthrodesis Stability with Degree of Joint Fusion on MDCT

Abstract: After arthrodesis of the ankle or subtalar joint, MDCT scans can be used to determine whether that joint is likely to be stable if > 33% of the joint has visible bone fusion on sagittal MDCT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 9 publications
2
38
0
1
Order By: Relevance
“…The authors arbitrarily defined a CT finding of nonunion as 0-33% fusion on CT, partial union as 34-66% fusion, and complete union as 67-100% fusion. Dorsey et al, in a recent CT study, confirmed that a 33% CT fusion ratio threshold could accurately discriminate between clinical stability and instability [6]. Our study confirms these findings, as we found a globally low rate of bone fusion at between 33% and 50% in the majority of clinically stable patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The authors arbitrarily defined a CT finding of nonunion as 0-33% fusion on CT, partial union as 34-66% fusion, and complete union as 67-100% fusion. Dorsey et al, in a recent CT study, confirmed that a 33% CT fusion ratio threshold could accurately discriminate between clinical stability and instability [6]. Our study confirms these findings, as we found a globally low rate of bone fusion at between 33% and 50% in the majority of clinically stable patients.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of persistent radiolucency crossing the entire joint space at six months combined with loosening, bending, or breakage of fixation screws are still a highly specific sign of arthrodesis nonunion but these signs are rarely present and were never found in our non-union cases. Moreover, we believe as does Dorsey [6] that a small number of asymptomatic patients can have a low percentage of bone fusion after attempted arthrodesis. We report the first study in which the results of an arthroscopic subtalar posterior arthrodesis have been studied with a CT-scan rather than plain radiography.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar techniques have been used by other investigators in foot and ankle arthrodesis studies. 9,11,17,28 When compared to autograft, the B2A-granule group had a trend for a higher radiographic fusion rate (100% vs 92%) at 6-month follow-up as defined by evidence of bridging bone over at least 50% of the joint. The fusion rates for B2A-granules in the current study were higher than those observed in the pilot study of Daniels et al 7 using rhPDGF-BB, which showed a fusion rate of 75% (44/59) at 36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This notion has spurred the increasing use of computed tomography (CT) evaluation for arthrodesis in the orthopaedic community. 1,3,10 In a recent study evaluating 15 patients who had undergone hindfoot fusion, it was found that CT scan was a better modality for evaluating the extent of fusion in the hindfoot. Specifically, the CT scan could delineate the area of trabecular bridging at a given arthrodesis site more clearly.…”
Section: (Original) Clinical Research Articlementioning
confidence: 99%